Hardware-in-the-loop simulation of automatic steering control for lanekeeping manoeuvre: outer-loop and inner-loop control design. (22nd September 2010) - Ping, Em Poh; Hudha, Khisbullah; Jamaluddin, Hishamuddin
This paper presents a 9 Degree-of-Freedom (DOF) vehicle model combined with a closed-loop driver model for developing vehicle lateral control. The proposed driver model consists of a yaw effect adaptive fuzzy logic control. Stepper Motor Actuated Steering (SMAS) system is briefly introduced as an inner-loop subsystem. The Software-in-the-Loop (SILS) and Hardware-in-the-Loop (HILS) results show that the proposed driver model is capable of improving the Y-axis trajectory error and Y-axis trajectory manoeuvres significantly and the proposed SMAS system is capable of tracking the desired steering angle position and producing the front wheel angle for the use of vehicle model.